Clinical Outcome of Medial Meniscal Posterior Root Tear Repaired by Arthroscopic Transtibial Pull-through Technique in a Middle-aged Population – A Case Series - Selvaraj Ramalingam; K. Arvind Kumar; Gopinath Duraisamy; P. Stephen Bush (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Patients with partial meniscectomy for MMPRTs still develop early osteoarthritis, have poor clinical outcomes, and have a high arthroplasty rate at a follow-up of 8 more than 5 years. Aim: The aim of this study was to evaluate the clinical outcome of medial meniscal posterior root tears treated with arthroscopic transtibial pull-through technique in a middle-aged population. Materials and Methods: Patients with medial meniscus posterior root tears admitted to our facility between 2020 and 2022 were included in this study. The patients were subjected to radiological evaluation of X-rays preoperatively. All the patients were followed for 1 year and assessed using the Tegner Lysholm score. Results: Ten patients with medial meniscal posterior root tears were included in this study. We observed that eight patients who underwent posterior meniscal root repair had excellent results, and two patients had good results. Conclusion: Arthroscopic repair of posterior meniscal root tear shows a significant improvement in clinical outcome.